Isolation of Staphylococcus from bovine mastitis and their antibiotic sensitivity pattern - Baghel, A.; Chhabra, D.; Sharda, R.; Shukla, S.; Audarya, S.; Sikrodia, R.; Gangil, R. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A total of 300 milk samples from cows and buffaloes were evaluated for mastitis and incidence of Staphylococcus. Overall, 131 milk samples (43.6%) were found positive for mastitis and out of these positive isolates, 47 bacterial isolates (35.87%) were identified as Staphylococcus. All the 47 isolates of Staphylococcus were tested for in vitro sensitivity towards 15 antibacterial drugs. The highest resistance was attributed towards antibiotic Ampicillin followed by Methicillin, Oxacillin, Ceftriaxone, Rifampicin, Vancomycin, Amoxyclave, Oxytetracycline, Erythromycin, Nitrofurantoin, Cefuroxime, Gentamicin, Norfloxacin, Ciprofloxacin and Levofloxacin. The sensitivity of bacterial isolates against various groups of antibiotics revealed Quinolones to be most efficacious.
Keywords: AST; antibiotics; mastitis